PENERAPAN BACKPROPAGATION DALAM MEMPREDIKSI PRODUKSI KELAPA SAWIT UNIT KEBUN MARJANDI - Azlan Zulhamsyah; Saifullah Saifullah; Muhammad Ridwan Lubis (STMIK Budi Darma, 2019)
Oil palm plantations are one of the types of plantation crops that occupy an important position in the agricultural sector in general, and the plantation sector in particular